Leading with Feminist Care Ethics in Higher Education Experiences, Practices, and Possibilities - Schultz, Christie (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"Leading with Feminist Care Ethics is a compelling reading experience, as the presence of the author in dialogue with both the theoretical material and the case studies she conducts pulls the reader into deeper consideration of both the ethics and the practicalities of care as a component of leadership roles in higher education. The book, its conversations, and its methodology work together to explore the complex relationship between care and the university-the university as a community that requires care in order to thrive; the university as an institution that can teach care as a component of its work; and the university as an institution that sometimes abuses care among its most committed members." -Kathleen Fitzpatrick, Director of Digital Humanities and Professor of English, Michigan State University, USA "Higher education, and leadership in higher education, is in transition. Including a feminist care ethics approach within this transition is needed if we are to consider a better, more caring, future. Schultz's work offers us a way to begin to understand the lived experiences of care ethics for leaders in higher education." -Heather Zwicker, Executive Dean, Faculty of Humanities and Social Sciences, The University of Queensland, Australia This book explores how academic leaders throughout higher education experience and practice care and the ethics of care. Drawing on a narrative inquiry study of experiences and practices of feminist care ethics in higher education leadership, Schultz counters academic norms, including expectations of competition and criticism across all activities, by uncovering the common experiences of academic leaders who intentionally adopt practices guided by an ethics of care and relationality. Within the context of institutions of higher education responding to present-day social movements, the book highlights how practices of care-centered leadership can enable change that begins on campus and reaches outwards to positively impact the community. Christie Schultz is Dean of the Centre for Continuing Education and Associate Professor in the Faculty of Education at the University of Regina, Canada. She is a scholar of leadership in higher education, care ethics in leadership, and qualitative research methodologies-especially narrative inquiry.
Part I Introduction -- 1 Coming to Care Ethics in Higher Education -- Theme and Scope -- Coming to a Research Puzzle: A Narrative Beginning -- Foregrounding Personal Justifications -- Feminist Care Ethics as a Theoretical Framework -- My Earliest Stories Linking Care and Higher Education -- Noddings's Language of Care -- Using Narrative Inquiry to Understand Leadership Experiences and Practices -- Narrative Inquiry's Methodological Commitments -- Research Design Summary -- Methodological Characteristics and Considerations -- Towards an Understanding of Experiences, Practices, and Possibilities -- References -- 2 Care Ethics that Matter -- Practical Justifications -- Contextualizing Change -- Higher Education in Neoliberal Times -- Higher Education Leadership -- Social Justifications -- Care in Education -- Care in Higher Education -- Tensions -- (En)Countering the First Tension: Organizations as Obstacles to Care -- (En)Countering the Second Tension: Leadership as a Barrier to Care -- (En)Countering the Third Tension: Gendered Care and Caring -- Beginning to Understand Care Ethics in Higher Education Leadership -- References -- Part II Stories of Experiences and Practices of Care-Centered Leadership -- 3 Beth -- Introducing Beth -- Beginning in the Middle -- Where Care Comes From -- Beginning Again -- Weaving Care and Self-Care -- As Care Seeks and (Sometimes) Finds Visibility -- Being Cared For: Friendship and Feeling Seen -- Caring into the Future -- References -- 4 Lynn -- Introducing Lynn -- Connecting -- Journeying Towards Leadership -- Embracing Leadership -- Care in Her Midst -- The Relational Nature of Care -- Caring for the Work, Too -- Tending to Tensions, Too -- The Whole Self-Caring -- Self-Care and Rest -- Leaning into the Future -- Postscript -- Reference -- 5 Abby -- Introducing Abby -- Learning to Show Up, to Participate, and to Listen -- Learning to "Think on My Feet" -- "There Was No Care" -- Enacting Feminist Care and Care Ethics -- Deep Listening -- Being Genuine -- Caring and Chairing in Neoliberal Times -- Enabling Care, Now and into the Future -- Being Surrounded by Care -- Lighting the Way -- References -- 6 Genevieve -- Introducing Genevieve -- Beginnings -- The Work of Care -- The Hard Work of the Work of Care -- Receiving Care -- An Arc of Care and Not Care -- Creating Care -- Research as Self-Care -- Making Care Visible -- Feeling Cared for as a Leader -- Caring and Chairing -- Seeing Care -- Coda -- Reference -- Part III Towards Care-Centered Leadership in Higher Education -- 7 Resonant Threads -- Thinking with Resonant Threads -- Situating the Writing of the Resonant Threads -- Awakening to Three Resonant Threads -- Learning to Care: Awakening to Where Care Comes From -- Experiences of Care from Mentors -- Familial Experiences of Care -- With the Threads of This Resonance -- The Challenge of Care: Caring in Challenging Moments and Times -- The Limits of Care: Tensions in Challenging Moments -- The Labor of Care: Risking the Work of Care in Challenging Times -- With the Threads of This Resonance -- Care for the Self: A Condition of Care -- Care for the Self with Movement and Music -- Care for the Self with Research and Writing -- Care for the Self with Rest and Recalibration -- With the Threads of This Resonance -- References -- 8 Conclusion: Care-Centered Leadership in Our Midst -- Emerging Visibility of Care-Centered Leadership -- Making Care in Leadership in Higher Education Visible -- Revisiting Social, Practical, and Personal Justifications: Implications and Possibilities -- Revisiting Social Justifications: Social and Theoretical Implications and Possibilities -- Revisiting Practical Justifications: Practical Implications and Possibilities -- Revisiting Personal Justifications: Implications and What I Will Remember -- References -- Epilogue: Leading with Feminist Care Ethics in Times of Change.
Keywords: Education, Higher; School management and organization; School administration; Social service; Feminism; Feminist theory; Diversity in the workplace; Higher Education; Organization and Leadership; Social Care; Feminism and Feminist Theory; Diversity Management and Women in Business